Relation of Diabetes to Cognitive Function in Hispanics/Latinos of Diverse Backgrounds in the United States. (August 2019) - Elfassy, Tali; Aiello, Allison E.; Schneiderman, Neil; Haan, Mary N.; Tarraf, Wassim; González, Hector M.; Gellman, Marc; Florez, Hermes J.; Luchsinger, Jose A.; Wright, Clinton B.; Grober, Ellen; Zeki Al Hazzouri, Adina
Objectives: To examine the association between diabetes and cognitive function within U.S. Hispanics/Latinos of Central American, Cuban, Dominican, Mexican, Puerto Rican, and South American background.Method: This cross-sectional study included 9, 609 men and women (mean age = 56.5 years), who are members of the Hispanic Community Health Study/Study of Latinos. We classified participants as having diabetes, prediabetes, or normal glucose regulation. Participants underwent a neurocognitive battery consisting of tests of verbal fluency, delayed recall, and processing speed. Analyses were stratified by Hispanic/Latino subgroup.Results: From fully adjusted linear regression models, compared with having normal glucose regulation, having diabetes was associated with worse processing speed among Cubans (β = −1.99; 95% CI [confidence interval] = [−3.80, −0.19]) and Mexicans (β = −2.26; 95% CI = [−4.02, −0.51]). Compared with having normal glucose regulation, having prediabetes or diabetes was associated with worse delayed recall only among Mexicans (prediabetes: β = −0.34; 95% CI = [−0.63, −0.05] and diabetes: β = −0.41; 95% CI = [−0.79, −0.04]). No associations with verbal fluency.Discussion: The relationship between diabetes and cognitive function varied across Hispanic/Latino subgroup.